Bacterial growth stage determines the yields, protein composition, and periodontal pathogenicity of Porphyromonas gingivalis outer membrane vesicles - Mao, Hongchen; Gong, Ting; Sun, Yuting; Yang, Shiyao; Qiao, Xin; Yang, Deqin (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction P. gingivalis (W83), as the keystone pathogen in chronic periodontitis, has been found to be tightly bound to systemic diseases. Outer membrane vesicles (OMVs) produced by P. gingivalis (W83) are thought to serve key functions in bacterial virulence and pathogenicity. This study aims to comprehend the biological functions of P. gingivalis OMVs isolated from different growth stages by comparing their physicochemical properties and pathogenicity. Methods Protein composition was analyzed via isotope-labeled relative and absolute quantification (iTRAQ). Macrophage polarization and the expression of IL-6 and IL-1β were detected. The proliferation, migration, osteogenic differentiation, and IL-1b/NLRP3 expression of periodontal ligament stem cells (PDLSCs) were evaluated. P. gingivalis/P. gingivalis OMVs-induced periodontal models were also constructed in Sprague Dawley rats. Results The protein composition of P. gingivalis OMVs isolated from different growth stages demonstrated obvious differences ranging from 25 KDa to 75 KDa. In the results of flow cytometry, we found that in vitro experiments the M1 subtype of macrophages was more abundant in the late-log OMVs and stationary OMVs groups which boosted the production of inflammatory cytokines more than pre-log OMVs. Compared to pre-log OMVs, late-log OMVs and stationary OMVs had more pronounced inhibitory effects on proliferation, migration, and early osteogenesis of PDLSCs. The NLRP3 inflammasome was activated to a larger extent in the stationary OMVs group. Micro-computed tomography (Micro CT), hematoxylin-eosin staining (HE), and tartrate acid phosphatase (TRAP) results showed that the periodontal damage in the stationary OMVs group was worse than that in the pre-log OMVs and late-log OMVs group, but almost equal to that in the positive control group (P. gingivalis). Discussion In general, both in vivo and in vitro experiments showed that late-log OMVs and stationary OMVs have more significant pathogenicity in periodontal disease.